Analisis Pengaruh Strategi Pemasaran Digital terhadap Preferensi Belanja Generasi Z di Platform E-Commerce - Ibrahim, Fauziah; Nugrahaningsih, Hartanti (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
ABSTRACT The impact of digital technology development has driven significant changes in marketing strategies, particularly in the e-commerce sector. Generation Z, who grew up with the internet and social media, has become the primary target for various e-commerce platforms such as Tokopedia, Shopee, Lazada, and TikTok Shop. This study aims to analyze the influence of digital marketing strategies on Generation Z's shopping preferences on e-commerce platforms. The focus of digital marketing strategies in this study includes social media marketing, influencer marketing, ad personalization, online promotions, and user-generated content (UGC). This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS software. The respondents in this study are Generation Z aged 15–26 years who are active shoppers on e-commerce platforms. The results of the study indicate that not all digital marketing strategies have a significant impact on shopping preferences. Among the variables tested, user-generated content was found to have the most significant influence in increasing Generation Z's shopping tendencies, while influencer marketing and social media marketing showed positive but non-significant effects. These findings emphasize the importance of authentic content and consumer participation in shaping digital shopping preferences. This study provides strategic recommendations for e-commerce players to further optimize user-content-based approaches to attract and retain Generation Z consumers.